ASSESSING VALUATION MODEL FORECASTING ACCURACY IN HEALTHCARE: A SIMULATED COMPARISON OF CAPM AND DDM - Wil Martens (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study addresses the challenges of valuing firms in the volatile healthcare sector by rigorously comparing the fore- casting accuracy of the Capital Asset Pricing Model (CAPM) and the Dividend Discount Model (DDM). Employing a controlled synthetic dataset of 100 healthcare firms spanning 2019–2021, we aim to isolate model performance, free from real-world confounding factors. Forecast accuracy is measured using Mean Absolute Error (MAE) and Percent- age Absolute Error (PAE). Results indicate CAPM significantly outperforms DDM (e.g., CAPM’s average PAE of 3.47% vs. DDM’s 8.48%), particularly due to healthcare’s variable dividend policies. This research provides empirical evidence from a controlled setting on model suitability, guiding financial practitioners toward more reliable valuation techniques and contributing to the literature on model selection in sector-specific financial contexts.